Growth hormone STAT5-mediated signaling and its modulation in mice liver during the growth period - Martinez, Carolina Soledad (2013)
Postnatal growth exhibits two instances of rapid growth in mice: the first is perinatal and independent of growth hormone (GH), the second is peripuberal and GH-dependent. Signal transducer and activator of transcription 5b (STAT5b) is the main GH-signaling mediator and it is related to IGF1 synthesis and somatic growth. The aim of this work was to assess differential STAT5 sensitivity to GH during the growth period in mouse liver of both sexes. Three representative ages were selected: 1-week-old animals, in the GH-independent phase of growth; 2.5-week-old mice, at the onset of the GH-dependent phase of growth; and 9-week-old young adults. GH-signaling mediators were assessed by immunoblotting, quantitative RT-PCR and immunohistochemistry. GH-induced STAT5 phosphorylation is low at one-week and maximal at 2.5-weeks of age when compared to young adults, accompanied by higher protein content at the onset of growth. Suppressor CIS and phosphatase PTP1B exhibit high levels in one-week animals, which gradually decline, while SOCS2 and SOCS3 display higher levels at adulthood. Nuclear phosphorylated STAT5 is low in one-week animals while in 2.5-week animals is similar to 9-week control, expression of SOCS3, an early response GH-target gene, mimics this pattern. STAT5 coactivators glucocorticoid receptor (GR) and hepatic nuclear factor 1 (HNF1) abundance is higher in adulthood. Therefore, GH-induced STAT5 signaling presents age-dependent activity in liver, with its maximum coinciding with the onset of GH-dependent phase of growth, accompanied by an age-dependent variation of modulating factors. This work contributes to elucidate the molecular mechanisms implicated in GH responsiveness during growth.